Examine the Incidence and Predictors of Neonatal Surgical Mortality - Asad Iqbal, Gauri Shankar Pandit, Muhammad Tayyab Azam, Nahida Burki, Hafiz Mubashir Rasool, Safina Karim, Ranjana Kumari Pandit, Nadeem Akhtar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Aim of current study is to determine the incidence and predictors of neonatal surgical mortality. Study Design: Observational/Prospective study Place and Duration: Children Hospital PIMS.Nov-2021-April 2022 Methods: There were 130 neonates were presented in this study. Included neonates had age 1-25 days admitted to hospital for thoracic and abdominal surgery. After getting informed written consent from the parents, detailed demographics of neonates delivery was recorded. Frequency of mortality and its predictors were assessed in this study. SPSS 23.0 was used to analyze all data. Results: Among 130 neonates, 80 (61.5%) were male neonates and 50 (38.5%) were females. Mean gestational age at delivery was 35.4 ±11.9 weeks and mean age at surgery was 11.8±4.52 days. Mean weight at birth was 2.10±1.27 kg. Frequency of abdominal surgery was found in 70 (53.8%) cases, followed by thoracic surgery in 35 (36.9%) cases and superficial surgery in 25 (19.2%) cases. Frequency of mortality was found in 41 (31.5%) neonates. Predictors of mortality was prolong duration of surgery, higher ISS >10, gestation age <36weeks, prolong ventilation, re-operations, high vasopressors and low birth weight with p value <0.004. Conclusion: The incidence of NSM was found to be highly reliant on both preoperative stress and postoperative treatment. As the margin for error in neonatal surgery is so small, skilled professionals are required to ensure the best possible outcomes and the shortest possible operating times. Our findings encourage the development of a risk classification score for neonatal operations. Keywords: Surgical Neonates, Complications, Mortality, Predictors